Domination in the communal space. Issue 1 (April 2020) - Siagian, M; Sitorus, R; Eddy, F
Abstract: Space is an integral aspect of individual identity-forming, group and social. Some incidents at the Fakultas Pertanian (FP), one of 15 faculties in Universitas Sumatera Utara (USU), show the space used as a tool and where students display the identity of the group. Communal space domination becomes a strategy used as a seniority identity. Junior students choose to step away from the senior space. Domination is a form of asymmetric power relations where the dominated subject has limited space to maneuver the choice of action. This dominant group predisposed to structure themselves as group-based social hierarchies and that the major forms of group oppression, prejudice, and discrimination. University is intended as a place where ideas, people, majors, in contrast to the concept of domination occur in the FP area. But senior domination through space strengthening the relationship between alumni after graduate students. By the qualitative research method, the research is done by supervision, questioning and answering with the student repeatedly. This paper explains how the concept of domination of the space succeeded in strengthening the relationship between groups when junior willingly it happened so that the experience of this event is interpreted as a way to build the next relationship.